GAMBARAN HEMATOLOGI PADA PASIEN SINDROM KORONER AKUT YANG DIRAWAT DI BLU RSUP PROF. Dr. R.D. KANDOU MANADO TAHUN 2010 - Ramadhani, Bagus Yuvi Setyo; Rotty, Linda W.A; Wantania, Frans (Universitas Sam Ratulangi, 2013)
Abstract: Acute coronary syndrome (ACS) is a series of clinical disorders caused by acute ischemic heart disease, including angina unstable, non-ST elevation myocardial infarction, and ST-elevation myocardial infarction. This study aimed to determine the relationship of routine hematological changes with the course of acute coronary syndromes. We used a descriptive method. Data were obtained from the secondary data of ACS patients in the ICCU RSUP Prof. Dr. R. D. Kandou Manado during 2010. The data were presented in distributive tables. The results showed that most patients did not experience decreases in hematological parameters such as hemoglobin, hematocrite, erythrocyte counts, and platelet counts. The leucocyte counts increased in 50% of cases. Conclusion: In general, there was no decrease in hematological parameters, except leukocyte counts, among the ACS patients in the ICCU RSUP Prof. Dr. R. D. Kandou Manado during 2010. Keywords: acute coronary syndrome, coronary heart disease, hematology, inflammation Abstrak: Sindrom koroner akut (SKA) merupakan rangkaian gangguan klinis yang disebabkan oleh penyakit akut iskemik jantung, termasuk angina tidak stabil, non-ST elevasi miocard infraction, dan ST-elevasi miocard infraction. Penelitian ini bertujuan untuk mengetahui hubungan perubahan hematologi rutin dengan perjalanan penyakit sindrom koroner akut. Penelitian ini memakai metode deskriptif dengan menggunakan data sekunder dari penderita SKA di ruang ICCU RSUP Prof. Dr. R. D. Kandou Manado selama tahun 2010. Data hasil penelitian disajikan dalam bentuk tabel distributif. Hasil penelitian Â memperlihatkan bahwa sebagian besar pasien tidak memperlihatkan penurunan parameter hematologi. Jumlah leukosit meningkat pada 50% kasus. Simpulan: Umumnya tidak terdapat penurunan parameter hematologi, kecuali jumlah leukosit pada pasien SKA ruang ICCU RSUP Prof. Dr. R. D. Kandou Manado selama tahun 2010. Kata kunci: Sindrom koroner akut, penjakit jantung koroner, Hematologi, inflamasi